Islamic Education Based Moderation as a Counter Narrative to Contemporary Social Intolerance - Wildan Miftahussurur; Ibnu Imam Al Ayyubi; Nurhikmah; Alamul Huda Almuzakky (Al-Bustan: Jurnal Pendidikan Islam, 2026)
Moderation is an important strategy in facing the challenges of social diversity in various modern communities. This study aims to analyze religious moderation as a counter-narrative to intolerance within society. The research employed a descriptive qualitative approach with purposive sampling techniques. Data were collected through in-depth interviews, observation, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that religious moderation is not merely understood as a normative concept but is manifested in everyday social practices through tolerance, mutual respect, and the refusal to impose religious beliefs on others. Differences both interfaith and intra-faith, such as those between NU and PERSIS communities, are managed peacefully through dialogue and respect for individual convictions. Intolerance is largely perceived as stemming from religious ego and exclusive truth claims rather than from religious teachings themselves. Religious moderation thus functions as a social mechanism to prevent conflict and maintain social harmony. The study also highlights the crucial role of religious leaders, community figures, and digital literacy in countering intolerant narratives in the era of social media. Therefore, religious moderation serves as a relevant social strategy for strengthening unity and cohesion in a pluralistic society.